The crystal structure of 17-(bromoethynyl)-17-hydroxy-10, 13-dimethyl- 1,2,6,7,8,9,10,11,12,13,14,15,16,17-tetradecahydro-3H-cyclopenta[a]phenanthren-3-one, C21H27BrO2 - Ji Xiao-Liang; Xie Feng; Li Yi-Biao (Zeitschrift für Kristallographie - New Crystal Structures)
C21H27BrO2, monoclinic, P21 (no. 4), a = 6.6220(14) Å, b = 11.7640(2) Å, c = 11.8485(2) Å, β = 95.0757(19)° V = 919.39(3) Å3, Z = 2, Rgt(F) = 0.0264, wRref(F2) = 0.0695, T = 150 K, Flack-parameter = 0.007(13).